2014
DOI: 10.4103/1658-354x.130727
|View full text |Cite|
|
Sign up to set email alerts
|

Pain relief after Arthroscopic Knee Surgery: A comparison of intra-articular ropivacaine, fentanyl, and dexmedetomidine: A prospective, double-blinded, randomized controlled study

Abstract: Background:Postoperative pain is very common distressing symptom after any surgical procedure. Different drugs in different routes have been used for controlling post-arthroscopic pain. No one proved to be ideal. We have compared the analgesic effect of ropivacaine, fentanyl, and dexmedetomidine when administered through the intra-articular route in arthroscopic knee surgery.Materials and Methods:From March 2008 to July 2010, 99 patients undergoing arthroscopic knee surgery were randomly assigned into three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…who used dexmedetomidine, fentanyl, and ropivacaine through intraarticular route. [ 23 ] Analgesia provided postoperatively by subarachnoid block may have contributed to the delayed request for analgesia in comparison to our study, in which general anesthesia was used in all patients.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…who used dexmedetomidine, fentanyl, and ropivacaine through intraarticular route. [ 23 ] Analgesia provided postoperatively by subarachnoid block may have contributed to the delayed request for analgesia in comparison to our study, in which general anesthesia was used in all patients.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have evaluated the analgesic efficacy of dexmedetomidine through intraarticular, intravenous routes, and buccal/intramuscular premedication for knee arthroscopies. [ 3 20 21 22 23 24 25 26 27 ] However, we are unaware of any study that has tried to evaluate the adjunctive use of intravenous dexmedetomidine with intraarticular bupivacaine in arthroscopic knee surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Manuar M et al in their study compared intraarticular ropivacaine ,fentanyl and dexmedetomidine for pain relief and suggested that ropivacaine was better than both fentanyl and dexmedetomidine. 17 From above studies it can be summarized that intra-articular fentanyl alone cannot produce prolonged analgesia. But dexmedetomidine alone can be used as a potent intraarticular analgesic for postoperative pain management.…”
Section: Discussionmentioning
confidence: 99%